Regularização fundiária rural na Amazônia legal: análise de uma política de contrarreforma agrária - Caetano, Camilla Amaral de Paula (2019)
The present dissertation aimed to analyze the current legal construction on the Brazilian land regularization, with emphasis on the Legal Amazon, as well as the norms that strengthen a kind of agrarian counter-regulation policy. The central analysis consisted of examining the role of the institutions in the implementation of the new land settlement policy, as provided for in Law nº 3.465/2017, as the work discusses may stifle the Brazilian agrarian reform. The methodological techniques of bibliographic research and documentary research were used, with analysis of data produced by the Special Secretariat of Family Agriculture, INCRA and also by the Earth Pastoral Commission in their reports. We also turn our attention to the legislation on the subject, beyond the jurisprudence and the study of regularization processes. For this, in the first chapter, it was sought to understand the Brazilian questiono n land, its occupation and the forms of appropriation over time, as well, as the modern conception of territoriality, focusing on the requirements for land regularisation and how the domain title is granted. Focusing mainly on the transformation of the land into merchandise and the identification of the land as a tool of occupation in the Legal Amazon. The second chapter, in turn, shows what were the legislative proposals for land regularization in the Legal Amazon. The analysis of the legislation makes a parallel between the arguments presented by the legislature at the time of the Bill versus the legal devices that make up the new Law nº 13.465/2017, especially with regard to the crucial points of the norm. These points are already objects of direct actions of unconstitutionality. In the third chapter, the analysis, turned to family farming and the Social Programmes for landuse regularisation for small farmers. The idea was to draw attention to the aspects that place the current legislation in the wake of those who, instead of potentiating the process of wesening reform, hinders it. It is these aspects that allow the conclusion that once again the legislation strengthens an agrarian counter-reaction process.